Chromosomal Aberration of Fasciola Hepatica Acetone Powder: In Vitro Study on Human Lymphocytes - Al- Bayati Saad Mohi Haider; Ali Mohammed Rafeik (Institute of Medico-legal Publications Pvt Ltd, 2021)
Fasciola hepatica metazoan trematodes parasite that is living in the liver of their host (sheep, goat andhuman). It usually cause pathological changes in the parasitized organs. Acetone powder technique is usedto prepare partially purified organic material of adult worms. Various concentrations of Fasciola hepaticaacetone extract (5 mg/ml, 10 mg /ml , 15mg/ml , 20 mg/ml and 40 mg /ml) are used on human lymphocyteculture for studying some chromosomal aberration. Chromosomal aberrations includes Isogap, Breaks andDicentrics for chromosomes; Gaps and deletion for chromatids; and mitotic index (MI). This In-vitro studyrevealed that acetone powder extract of Fasciola hepatica parasites causing various genotoxicity effects inthe human lymphocyte cells. These effects are ascending in their increasing in significance differences (P<0.001) for all treatment against control as concentration of acetone extract is increased.